2020
DOI: 10.3847/1538-4357/abb6e7
|View full text |Cite
|
Sign up to set email alerts
|

Piercing through Highly Obscured and Compton-thick AGNs in the Chandra Deep Fields. II. Are Highly Obscured AGNs the Missing Link in the Merger-triggered AGN–Galaxy Coevolution Models?

Abstract: By using a large, highly obscured ( > -N 10 cm H 23

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 160 publications
0
7
0
Order By: Relevance
“…Moreover, depending upon the selection criteria, the resulting MIR AGN sample may be contaminated by star-forming galaxies, especially for the criterion in Lacy et al (2007). The criterion in Donley et al (2012) is generally more reliable in avoiding the misclassification of star-forming galaxies as AGNs, but it may miss the highly obscured AGNs (e.g., Li et al 2020). In this work, we select MIR AGN candidates if a source is detected in all four IRAC bands with a signal-to-noise ratio (S/N) above three and meets any criterion in Stern et al (2005), Lacy et al (2007), or Donley et al (2012) so that the resulting MIR AGN sample is as complete as possible.…”
Section: An Overview Of Different Selection Methodsmentioning
confidence: 99%
“…Moreover, depending upon the selection criteria, the resulting MIR AGN sample may be contaminated by star-forming galaxies, especially for the criterion in Lacy et al (2007). The criterion in Donley et al (2012) is generally more reliable in avoiding the misclassification of star-forming galaxies as AGNs, but it may miss the highly obscured AGNs (e.g., Li et al 2020). In this work, we select MIR AGN candidates if a source is detected in all four IRAC bands with a signal-to-noise ratio (S/N) above three and meets any criterion in Stern et al (2005), Lacy et al (2007), or Donley et al (2012) so that the resulting MIR AGN sample is as complete as possible.…”
Section: An Overview Of Different Selection Methodsmentioning
confidence: 99%
“…With these observations, accurate estimates of N H and intrinsic X-ray luminosity can be made. Li et al (2020) improved this analysis for the most heavily obscured AGNs within CDF-N/S. Estimates of the intrinsic X-ray luminosity and column density are taken from Li et al (2020) when available.…”
Section: Goodsmentioning
confidence: 99%
“…SFRs estimated from far-IR luminosities have been used to conclude that quasar host galaxies tend to lie on or near to the star-forming galaxy main sequence [25,49,91,158,198,251,258,328,339]. However, Xie et al [326] recently concluded that AGN hosts predominantly lie above the main sequence.…”
Section: Star Formationmentioning
confidence: 99%